Protection of the Mediterranean Sea - Jennifer Clapp (The Encyclopedia of Conservation and Environmentalism, 1995)
Focusing on both problems and solutions, this authoritative reference work maintains a healthy balance between science and the social sciences in its coverage of all aspects of the environment. The book is arranged alphabetically and is divided into three major sections: Ecology, Pollution, and Sustainability. The list of 240 contributors reads like a who's who of the world's leading conservation and environmental professionals.